River Valley Tourism Space - Wiluś, Robert (Turyzm/Tourism, 2007)
Contemporary tourism is strongly related to water areas as water is one of the most popular tourism assets. Tourism in water areas creates a tourism space whose extent, structure and size depend mostly on access to water and the possibility of using it for tourism. Compared to seas or lakes, rivers are water areas not heavily exploited by tourism. The article presents the relation between tourism development and the particular river-valley system which creates river valley tourism space. This space is diversified both along the river and in the cross-section of the valley.